Building Oracle XML applications - Muench, Steve (O'Reilly, 2000)
This rich and detailed look at the many Oracle tools that support XML development shows Java and PL/SQL developers how to combine the power of XML and XSLT with the speed, functionality, and reliability of the Oracle database. The nearly 800 pages of entertaining text, helpful and time-saving hints, and extensive examples can be put to use immediately to build custom XML applications. Includes a CD-ROM with JDeveloper 3.1, an integrated development environment for Java developers.